STABILISASI TANAH CAMPURAN VOLCANIC ASH TERHADAP NILAI KUAT GESER PADA TANAH QUARRY MEUNASAH RAYEUK KAWAY XVI ACEH BARAT - Reza Mulia; Munirwansyah; Devi Sundary (Construction and Material Journal, 2023)
A clay-silty located in the quarry Meunasah Rayeuk, Kaway XVI, West Aceh is a source of stockpile material that is often used as road construction material in West Aceh. Based on the color this land is divided into three, namely red, yellow, and gray soil. These three types of soil have bad properties that make them unfit for use as road base layers. Therefore, it is necessary to stabilize it with a mixture of volcanic ash taken from Wih Pesam, Bener Meriah. The purpose of this study was to determine the effect of mixing soil with volcanic ash on the shear strength of the soil. This research method was carried out in the form of standard compaction tests, and direct shear strength on mixed volcanic ash soils. Variations in the addition of volcanic ash are 12.5%, 15%, 17.5%, and 20% of the dry weight of the soil. The research results show that these types of soil belonged to the A-7-6 of soil classification according to AASHTO identified as containing montmorillonite minerals in gray soil. The addition of volcanic ash to the three types of soil can increase the value of the shear strength of the original conditions at certain variations. The results of shear strength values ​​for volcanic ash mixture variations of 0%, 12.5%, 15%, 17.5% and 20%, were 0,8, 1,0, 0,8, 1,0, and 0,7 in units of kg/cm2 for red soil respectively. In the yellow soil of 1,0, 1,0, 0,9, 1,2, and 0,9 in units of kg/cm2. On gray soil as much as 0,7, 1,1, 1,0, 0,9, and 1,1 in units of kg/cm2.